Does cutting a plaster window weaken its strength?. Issue 3 (March 2017) - Patel, Nimesh; Wilson, Lance; Wansbrough, Guy
Abstract: Introduction: A plaster window is usually created over a pressure area, or in some cases a wound or suture line. This can relieve pressure at the site, and provide an opportunity to change dressings, check on drainage, and inspect a wound or ulcer. There is concern that this can have an effect on its function to provide fracture stability, and weakens the plaster. The biomechanical effects of windowing on plaster strength were therefore investigated, as it has not previously been reported. Method: A laboratory study was undertaken to compare the bending, kinking and torsion loads withstood by standardised Plaster of Paris (POP), Softcast and Fibreglass casts compared to those with a 60 × 40 mm window fabricated in the centre at clinically defined endpoints using an Instron machine. Results: The addition of a window significantly weakened the load to failure of POP; Fibreglass, and Softcast by 23.1% (473.1N); 25.9% (401.8N), and 29% (146.6N) respectively, during the 4-point bending tests. During the 3-point kinking tests, load to failure was reduced by 38.5% (297.8N); 35.3% (146.9N), and 51.5% (103.8N) respectively. All tests were checked for consistency and carried out in a single orthogonal plane for ease of comparison. Discussion: The addition of a 60 × 40 mm window to a cast made up of POP, Fibreglass or Softcast weakens the cast load to failure by up to 51% against a 3-point loading force. Though windowing of casts is necessary in certain situations, we advise precautions such as adding further layers of plaster to the window site, keeping the window as small as possible, and advising the patient of the increased risk of weakening and failure of the plaster so that they can take more care.